Analysis of Murabahah Financing Strategy in Increasing the Number of Members: A Case Study on BMT (Baitul Mal Wal Tanwil) Permata Indonesia Pekanbaru Riau - Zulfikar Hasan; Amelia Ripal; Rino Riyaldi; Said Rizki Suhendra; Angga Dasma Hendra; Nur Hidayati (Jurnal Adijaya Multidisplin, 2023)
Market competition is not only in competition for goods but also in market competition; the presence of BMT, which survives and increasingly develops its market share, must have a strategy to achieve optimal profits. BMT (Baitul Mal Wal Tanwil) must determine every system appropriate for the goals, opportunities, expertise and human resources in the development of BMT for good promotion. The marketing strategy is the spearhead of a marketing plan that is made and is very necessary for a company that aims so that the projects completed can be carried out and achieved following predetermined goals, especially at BMT Permata Indonesia Pekanbaru, which is located at Jl. Rawamangun No. 67 Tangkerang Labui, Bukit Raya District, Pekanbaru. The population in this study were five people consisting of leaders, managers, marketing and two employees. The data collection technique uses purposive sampling, with descriptive data analysis such as interviews, observations, and documentation. Based on the study results, it can be concluded that the murabahah financing marketing strategy used by BMT Permata Indonesia Pekanbaru in increasing the number of members in place, product, price, promotion, people, and process—) and service. As for the weakness at BMT Permata Indonesia Pekanbaru, the lack of direct information and education from the community and understanding of the community has resulted in the absence of public interest in financing.